2017
DOI: 10.1681/asn.2017040421
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Changes in Human Kidneys with Healthy Aging

Abstract: Aging is associated with significant changes in structure and function of the kidney, even in the absence of age-related comorbidities. On the macrostructural level, kidney cortical volume decreases, surface roughness increases, and the number and size of simple renal cysts increase with age. On the microstructural level, the histologic signs of nephrosclerosis (arteriosclerosis/arteriolosclerosis, global glomerulosclerosis, interstitial fibrosis, and tubular atrophy) all increase with age. The decline of neph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
223
2
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(253 citation statements)
references
References 53 publications
7
223
2
9
Order By: Relevance
“…Although renal AS might be associated with concurrent HT, it is sometimes found even in patients without HT. Previous studies showed that renal AS was associated with aging, postprandial hyperglycemia and hyperinsulinemia, low serum high‐density lipoprotein cholesterol, hyperuricemia, and chronic inflammation. In contrast, a BP <140/90 mmHg is recommended to reduce ESRD and cardiovascular disease among people with diabetes in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although renal AS might be associated with concurrent HT, it is sometimes found even in patients without HT. Previous studies showed that renal AS was associated with aging, postprandial hyperglycemia and hyperinsulinemia, low serum high‐density lipoprotein cholesterol, hyperuricemia, and chronic inflammation. In contrast, a BP <140/90 mmHg is recommended to reduce ESRD and cardiovascular disease among people with diabetes in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Intrarenal arteriolosclerosis, which is thought to result in glomerulosclerosis with atrophy of the attached tubules and adjacent interstitial fibrosis, is a common vascular lesion in patients with kidney disease and is significantly correlated with age . In a study that analyzed 1450 renal biopsies, the incidence of vascular lesions among 222 patients under 40 years of age was 20.3% compared to 6.2% in controls of similar age; in patients aged 40 to 65 years and those older than 65, vascular lesions were found in 50% to 60% and 80.8% of the patients, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Intrarenal arteriolosclerosis, defined as fibrous and/or hyalinosis thickening of the intima, is observed in many different situations, including aging, hypertension, diabetes mellitus, idiopathic membranous nephropathy and focal segmental glomerulosclerosis . For patients with immunoglobulin A (IgA) nephropathy, intrarenal vascular sclerosis is present in 1 of 3 of initial biopsies .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Simple cysts are considered to be part of the regular aging process and are common in adults . The number of cysts may also increase with age.…”
mentioning
confidence: 99%